The role of corporate social responsibilty in strengthening stakeholders and public relationship with Sabah Credit Corporation / Kristy Kadius - Kadius, Kristy (Faculty of Business and Management, 2009)
This study was conducted to evaluate the role of corporate social responsibility (CSR) in strengthening the stakeholders and public relationship with Sabah Credit Corporation (SCC).The reason for conducting this study is because through this study SCC will know the effect of their CSR programme towards their organization and the stakeholder. The research design was used in this study is descriptive research in which primary data as well secondary data were gathered. The respondents for this study were SCC customer and the public in Penampang, Sabah. From this study, it is found that the public and the stakeholders were not aware and only a few of them have little knowledge about the Corporate Social Responsibility Program carried out by SCC. Therefore, SCC should give more exposure of their CSR program to the stakeholder and public such as give more information in the SCC website. This study helps us to understand better of the role of Corporate Social Responsibility in an organization.